The impact of social media on the happiness of Chinese college students - Yingying Xu; Ratna Roshida Ab Razak; Meng Xiang (Heliyon, 2024)
Background: In the contemporary academic milieu, an array of erudite investigations has meticulously delved into the ramifications of social media paradigms on the nuances of modern societal interactions. Predominantly, these scholarly endeavors have harnessed quantitative methodologies to discern both the advantageous and detrimental implications of social media. Notwithstanding these extensive analyses, there appears to be a conspicuous lacuna in the literature about the subjective repercussions of social media on the well-being and contentment of tertiary education students. In light of this gap, the present qualitative exploration seeks to elucidate the perceptions of Chinese collegiate individuals vis-à-vis the influence of social media platforms on their experiential happiness. Method: Guided by interpretative phenomenological analysis (Jonathan et al., 2022) [1], we conducted 3 semi-structured interviews with 5 university students. Result: Using an interpretive phenomenology analysis approach four themes. They are (1) The Paradox of Temperance and Indulgence, (2) Identity Construction and Presentation, (3) Social Support and Connection, and (4) Social Comparison and Self-Evaluation. Discussion: Findings suggest that the individual well-being of college students may be affected by ambivalence between moderate and indulgent use of social media, social media interactions to maintain and enhance personal identity, and comparisons between individuals and certain online groups. Therefore, the government, higher education institutions, and college students should work together to build a safe and happy university life.